Direct capture, inhibition and crystal structure of HsaD (Rv3569c) from M. tuberculosis. (13th October 2022) - Barelier, Sarah; Avellan, Romain; Gnawali, Giri Raj; Fourquet, Patrick; Roig‐Zamboni, Véronique; Poncin, Isabelle; Point, Vanessa; Bourne, Yves; Audebert, Stéphane; Camoin, Luc; Spilling, Christopher D.; Canaan, Stéphane; et al.
Abstract : A hallmark of Mycobacterium tuberculosis ( M. tb ), the aetiologic agent of tuberculosis, is its ability to metabolise host‐derived lipids. However, the enzymes and mechanisms underlying such metabolism are still largely unknown. We previously reported that the Cyclophostin & Cyclipostins (CyC ) analogues, a new family of potent antimycobacterial molecules, react specifically and covalently with (Ser/Cys)‐based enzymes mostly involved in bacterial lipid metabolism. Here, we report the synthesis of new CyC alkyne‐containing inhibitors (CyC yne ) and their use for the direct fishing of target proteins in M. tb culture via bio‐orthogonal click‐chemistry activity‐based protein profiling (CC‐ABPP). This approach led to the capture and identification of a variety of enzymes, and many of them involved in lipid or steroid metabolisms. One of the captured enzymes, HsaD (Rv3569c), is required for the survival of M. tb within macrophages and is thus a potential therapeutic target. This prompted us to further explore and validate, through a combination of biochemical and structural approaches, the specificity of HsaD inhibition by the CyC analogues. We confirmed that the CyC bind covalently to the catalytic Ser 114 residue, leading to a total loss of enzyme activity. These data were supported by the X‐ray structures of four HsaD‐CyC complexes, obtained at resolutions between 1.6 and 2.6 Å. The identification of mycobacterial enzymes directly captured by the CyC yne probes through CC‐ABPP paves the way to better understand and potentially target key players at crucial stages of the bacilli life cycle. Abstract : In this study, we used novel CyC yne inhibitor probes to directly capture and identify key mycobacterial enzymes in a Mycobacterium tuberculosis ( M. tb ) culture via bio‐orthogonal click‐chemistry activity‐based protein profiling. One of these enzymes, HsaD (Rv3569c), is required for M. tb survival within macrophages. The specificity of HsaD inhibition by various CyC analogues was deciphered and validated by X‐ray structures of four HsaD‐CyC complexes in the 1.6–2.6 Å resolution range.